Frequency response of the thyristor controlled series capacitor. - Daneshpooy, A. (IEEE Transactions on power delivery)
This paper introduces the application of a new method based on Fourier series expansion, to derive the frequency response of a thyristor controlled series capacitor (TCSC). The theory and the numerical approach are presented and the results are reported. Although this method is solely applied to the TCSC device in this context, it is completely general and may well be applied to any type of switched power device. The analysis shows the behavior of a TCSC at frequencies other than fundamental frequency. Such information is very important for sub-synchronous resonance (SSR) as well as other harmonic related studies